2006
DOI: 10.1108/02652320610659021
|View full text |Cite
|
Sign up to set email alerts
|

The effects of work‐family conflict, emotional exhaustion, and intrinsic motivation on job outcomes of front‐line employees

Abstract: PurposeThe purpose of this study is to investigate the effects of work‐family conflict, emotional exhaustion, and intrinsic motivation on front‐line employees' job performance, job satisfaction, and affective organizational commitment in Turkish retail banks as its setting.Design/methodology/approachA total number of 363 usable questionnaires were personally retrieved from front‐line employees in the research location. The relevant writings were canvassed in order to design the survey instrument. The hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
94
1
15

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(120 citation statements)
references
References 54 publications
(88 reference statements)
10
94
1
15
Order By: Relevance
“…This finding confirms the results of Halpern (2005), where meeting family obligations and work demands has caused mental strain among medical professionals, thus tallying with the other research where more married individuals were identified to be prone to the syndrome than the others. Having less time to spend with family and friends particularly due to the interference with work, correlated positively with the E.E dimension of the syndrome, thus confirming the pre -formed Hypothesis 2: Work -family conflict is positively correlated to burnout syndrome among medical professionals practicing at CSTH and Hypothesis 3: Work family conflict is positively correlated to the emotional exhaustion dimension of burnout syndrome .Furthermore this result conformed to the findings of Karatepe and Tekinkus (2006), where work family conflict was identified as a causative factor of E.E dimension of the syndrome.…”
Section: Discussion Of Findings Of the Validity Of The Pre -Establishsupporting
confidence: 80%
See 1 more Smart Citation
“…This finding confirms the results of Halpern (2005), where meeting family obligations and work demands has caused mental strain among medical professionals, thus tallying with the other research where more married individuals were identified to be prone to the syndrome than the others. Having less time to spend with family and friends particularly due to the interference with work, correlated positively with the E.E dimension of the syndrome, thus confirming the pre -formed Hypothesis 2: Work -family conflict is positively correlated to burnout syndrome among medical professionals practicing at CSTH and Hypothesis 3: Work family conflict is positively correlated to the emotional exhaustion dimension of burnout syndrome .Furthermore this result conformed to the findings of Karatepe and Tekinkus (2006), where work family conflict was identified as a causative factor of E.E dimension of the syndrome.…”
Section: Discussion Of Findings Of the Validity Of The Pre -Establishsupporting
confidence: 80%
“…With an increase in the number of hours worked and the corresponding work load, many medical professionals are faced with a dilemma of providing the necessary care to patients (Karatepe &Tekinkus, 2006). As a result the emotional exhaustion dimension of burnout syndrome and work family conflict seem to have a strong link as evident in the literature (Karatepe & Tekinkus, 2006).…”
Section: Work Family Conflictmentioning
confidence: 98%
“…The employees are the key factor in providing better service to their customers and ultimately it helps to improve the overall performance of the banks. The bank employees play an important role in delivering high quality services, promoting the corporate image and improving customer satisfaction (Karatepe and Tekinkus, 2006) [1]. According to Gabbott and Hogg (1997), employees' Job Performance (JP) is a key individual out-come in the financial and banking sector [2].…”
Section: Introductionmentioning
confidence: 99%
“…Job satisfaction has a positive relationship with organization commitment (Karatepe and Tekinkus, 2006) and organization commitment has a positive relationship with knowledge sharing (Jacobs and Roodt, 2007), therefore, job satisfaction may has a positive relationship with knowledge sharing (Rehman, Mahmood, Salleh, and Amin, 2010).…”
Section: Knowledge Sharing and Job Satisfactionmentioning
confidence: 99%